Strategic perspectives of outsourcing; The view within the insurance industry - Kapoor, Avya (2008)
Insurance companies have, for ages, outsourced claims settlement processes to third party service providers such as loss adjusters. Outsourcing in other industries is used as a strategic tool, but in the claims department of an insurance company, it is primarily done to acquire specialist skills to assist in the claims settlement process. While popular perception identifies off-shoring as the most effective way to trim business costs, this is not true for many reasons in the case of outsourcing claims management; the primary reason being, claims handling requires a very high level of expertise. The objective of this paper is to unearth the reasons and impact of outsourcing claims from the view of a loss adjusting company. The dissertation gives an insight into the practices in the insurance industry in India and UK, with special emphasis on considering outsourcing as an option for diversification for third party service providers. It shows the feasibility of outsourcing claims management with the help of perspectives of insurers and loss adjusters. The benefits of outsourcing claims, especially with respect to costs and expertise, are highlighted by means of a claims handling process for managing outsourced claims, which would increase efficiency of insurers. The objectives are achieved by using the Theory of Transaction Costs and the concept of core competencies. The methodology used for analysis also involves face-to-face interviews and e-mail interviews, with the experienced people in the insurance industry in India as well is in UK. These individuals, by virtue of their experience, have a strong grasp on the subject and can analyse the perspectives of off-shoring claims. Thus, combining the perspectives of the various players in the insurance sector and data collected from journals, we have analyzed the strategic perspectives of off-shoring claims.